KEMAMPUAN MENENTUKAN KONJUNGSI SUBORDINATIF KELAS VIII SMP IT AL-IZHAR SCHOOL PEKANBARU PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Tribowo H '; Mangatur Sinaga; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study, entitled The ability determines subordinating conjunctions IT class VIII students of Al-Izhar School Pekanbaru. This study aims to determine students' ability to determine the conjunctions in a sentence. The method used is descriptive analysis method. The research sample numbering 56. The results found (1) the percentage of subordinating conjunctions ability to determine the time of high category with a percentage of 84.18%, (2) ability to determine the percentage of subordinating conjunctions because high category with a percentage of 83.21%, (3) the percentage of ability determine the subordinating conjunctions supposition being categorized with the percentage of 78.21%, (4) ability to determine the percentage of subordinating conjunctions goal being categorized with the percentage of 81.61%, (5) ability to determine the percentage of subordinating conjunctions konsesif high category with a percentage of 86.10%, (6) ability to determine the percentage of subordinating conjunctions complementation being categorized with the percentage of 80.00%.Keywords: ability to determine , subordinating conjunctions , students viii